Relationships between human resource management practices, employees’ job satisfaction, and business performance in state-owned enterprises: A case study of enterprises in Vietnam posts and telecommunications group - Nguyen, Xuan Hiep; Nguyen, Thi Cam Loan (Journal of Finance - Marketing Research, 2022)
The study aims to explore and measure the relationships between human resource management practices, employees’ job satisfaction, and business performance in state-owned enterprises in Vietnam – A case study of enterprises in Vietnam Posts and Telecommunications Group (VNPT). The study adopts qualitative research, combined with quantitative research by CB-SEM The research data were collected from August 2021 to December 2021 by email and online survey with 621 staff currently working at VNPT in 18 provinces and cities representing 6 telecommunications service regions in nationwide Vietnam. The research results show that the human resource management practice at VNPT enterprises includes 7 components (job identification, recruitment, training and progression, performance appraisal, compensation, empowerment, and labor relations). They all have a strong influence on the employees’ job satisfaction and the business performance of VNPT enterprises. However, the influence of the employee’s job satisfaction on the business performance of these enterprises has not been found.